2021
DOI: 10.1016/j.parkreldis.2020.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level as a putative biomarker in Parkinson's disease patients carrying GBA1 mutations: 2-Year data from the PPMI study

Abstract: Blood uric acid represents an important biomarker in sporadic Parkinson's disease (PD). Whether uric acid levels change in genetic forms of PD is beginning to be assessed. The aim of the present study was to evaluate differences in serum uric acid level among PD patients harboring mutations in the glucocerebrosidase (GBA1) gene, sporadic PD, and healthy controls followed longitudinally. Methods: Longitudinal 2-year serum uric acid measurement data of 120 GBA-PD patients have been downloaded from the Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Interestingly, higher levels of serum UA are associated with a higher risk of developing PD in carriers of pathologic variants of the leucine-rich repeat kinase 2 (LRRK2) gene, the most common cause of familial PD [59], and these patients have lower levels of serum UA compared to healthy controls [60]. A significant association was also found between lower serum UA levels and the GBA1 mutation PD [61].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, higher levels of serum UA are associated with a higher risk of developing PD in carriers of pathologic variants of the leucine-rich repeat kinase 2 (LRRK2) gene, the most common cause of familial PD [59], and these patients have lower levels of serum UA compared to healthy controls [60]. A significant association was also found between lower serum UA levels and the GBA1 mutation PD [61].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that homozygote mutations of GBA can cause Gaucher disease, while heterozygous vectors are at risk for developing PD [9] . In previous studies, GBA1 mutation was associated with early-onset, the relatively symmetrical onset of limb symptoms, and faster motor and cognitive impairment progression in PD patients; however, the association between different GBA mutation subtypes are less studied [10] , [11] . It is noteworthy that former research has suggested that variants of GBA could be associated with faster progression of motor symptoms, accompanied by accelerated conversion to cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 94%
“…Ratios of each measure were also included as independent predictive variables. Total serum uric acid was also included as previously described 37 .…”
Section: Baseline Datamentioning
confidence: 99%